2017
DOI: 10.1177/0895904816682315
|View full text |Cite
|
Sign up to set email alerts
|

Raising the Bar on Teacher Quality: Assessing the Impact of Increasing Licensure Exam Cut-Scores

Abstract: State policy makers are constantly looking for ways to improve teacher quality. An oft tried method is to increase the rigor of licensure exams. This study utilizes state administrative data from Arkansas to determine whether raising the cut-scores on licensure exams would improve the quality of the teacher workforce. In addition, the study explores the trade-offs of such a policy decision. It is concluded that raising the required passing score on the Praxis II would increase the quality of the teacher workfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These exams provide a baseline standard of knowledge required to enter the profession and can include separate tests for measuring basic skills, content knowledge, and pedagogical knowledge (Goldhaber, Cowan, & Theobald, 2017; National Center for Education Statistics, 2017; Youngs et al, 2003). Certification exams can be seen as a barrier into the profession for individuals who do not exhibit a baseline standard of professional knowledge to become a teacher and could be used to increase the quality of individuals entering the profession (D’Agostino & Powers, 2009; Memory et al, 2003; Shuls, 2018). However, there has been some evidence that these exams disproportionately restrict teachers based on ethnicity (Angrist & Guryan, 2008; Goldhaber, 2007), gender (Goldhaber & Hansen, 2010; Rucinski & Goodman, 2019), and content area (Gitomer, 2007), and any evidence that associates these exams with teacher effectiveness has been marginal at best (Goldhaber, 2007; Goldhaber & Anthony, 2007; Goldhaber, Cowan, & Theobald, 2017; Goldhaber et al, 2013; Goldhaber & Hansen, 2010; Harris & Sass, 2011; Jacob & Walsh, 2011; Wayne & Youngs, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These exams provide a baseline standard of knowledge required to enter the profession and can include separate tests for measuring basic skills, content knowledge, and pedagogical knowledge (Goldhaber, Cowan, & Theobald, 2017; National Center for Education Statistics, 2017; Youngs et al, 2003). Certification exams can be seen as a barrier into the profession for individuals who do not exhibit a baseline standard of professional knowledge to become a teacher and could be used to increase the quality of individuals entering the profession (D’Agostino & Powers, 2009; Memory et al, 2003; Shuls, 2018). However, there has been some evidence that these exams disproportionately restrict teachers based on ethnicity (Angrist & Guryan, 2008; Goldhaber, 2007), gender (Goldhaber & Hansen, 2010; Rucinski & Goodman, 2019), and content area (Gitomer, 2007), and any evidence that associates these exams with teacher effectiveness has been marginal at best (Goldhaber, 2007; Goldhaber & Anthony, 2007; Goldhaber, Cowan, & Theobald, 2017; Goldhaber et al, 2013; Goldhaber & Hansen, 2010; Harris & Sass, 2011; Jacob & Walsh, 2011; Wayne & Youngs, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of occupations such as funeral provider, social worker, and certified public accountant have found licensing raises prices, in part through the aforementioned artificially increased wages (Pizzola and Tabarrok 2017), and produces little to no increase in quality (Bowblis and Smith 2018;Barrios 2018). Similarly, research on occupations such as midwife, cosmetologist, and teacher has shown more restrictive licensing regulations in the form of tighter scope-of-practice laws (Markowitz et al 2017), lengthier educational requirements (Simpson et al 2016), and higher minimum examination scores (Shuls 2017) do not lead to improved outcomes for consumers.…”
Section: Introductionmentioning
confidence: 99%
“…This literature is broad, spanning efforts to identify the attributes of strong teachers, to explore the nature and development of effective teaching practice, and to quantify the impacts of high-quality instruction on student learning. One major strand of the teacher-effectiveness research seeks to identify relationships between student achievement and proxy indicators of teacher quality--for instance, teacher characteristics like years of experience, training, and credentials (Cowan & Goldhaber, 2016;Darling-Hammond, 2000;Goldhaber & Anthony, 2007;Goldhaber, Lavery, & Theobald, 2015;Hattie, 2008;Huang & Moon, 2009;Kane, Rockoff, & Staiger, 2008;Rice, 2003;Shuls, 2018;Shuls & Trivitt, 2015;Vandevoort & Berliner, 2004). Few proxy measures have been demonstrated to reliably predict student achievement (Burroughs et al, 2019).…”
Section: Prior Research On Teacher Effectivenessmentioning
confidence: 99%